Study on the Thixotropy of the Fresh Concrete Using DEM. (2015) - Tan, Yuanqiang; Cao, Guodong; Zhang, Hao; Wang, Jiaqian; Deng, Rong; Xiao, Xiangwu; Wu, Binxing
Abstract: Fresh concrete is a typical thixotropy material with a time-dependent rheological characteristic. In this study, a general Discrete Element Method (DEM) model for the fresh concrete was firstly established and calibrated by the rheological tests with the contact parameters verified. Then, the thixotropy of the fresh concrete was considered by introducing a time-dependent contact parameter into the general DEM model. Based on the thixotropy DEM model, the lateral pressure of the fresh concrete on the wall was numerically investigated where the changing characteristic of the pressure over time was validated and the influence of thixotropy on the yield stress was addressed. The simulative results were found in accordance with the experimental observations, by means of which the capability of the established DEM model was demonstrated.